Occupancy of Javan Slow Loris (Nyticebus javanicus E. Geoffroy 1812) in Kemuning Tropical Low Land Forest, Bejen, Temanggung, Central Java - Mahfut Sodik; Satyawan Pudyatmoko; Pujo Semedi Hargo Yuwono (Jurnal Ilmu Kehutanan)
Habitat loss and landscape fragmentation have a negative impact on the Javan slow loris (Nycticebus javanicus), a Critically Endangered nocturnal primate species. Slow lorises in remaining forest fragments might be suffered and affect their occupancy behavior. We aim to investigate the determinant factors for the probability of habitat occupancy by the javan slow loris in Kemuning forest fragment of Temanggung District, Central Java. To estimate the site occupancy rate, detection probability, and the determinant factor of site use by Nycticebus javanicus, we employed the occupancy model of a single-season using night surveys. Five repeated night surveys in 2017 were used as the main basis data for the occupancy model. We used direct observation and interview with locals to collect data on environmental and anthropogenic features. We divided the study area into 141 grids with 200 m x 200 m (4 ha) each which were the basis for the night survey following existing walking paths. The influence of six covariates was assessed to determine of site use by Nycticebus javanicus: distance to road, distance to forest edge, distance to the settlement, distance to water source, altitude, and elevation. The result shows that the probability of site use occupied by Nycticebus javanicus was 23.2% of the total area. Distance to roads and distance to water source have a positive correlation with the probability of site use, whereas the influence of distance to settlements has a negative correlation with the site use of the species. Such quantitative data and information gained in this research are important to know for the long term resource needs of the Nycticebus javanicus, especially in the Kemuning forest. Therefore, the Indonesian Government or related stakeholders can formulate the detail conservation plans of the species, especially in the lowland fragmented tropical forest.